High burden of prediabetes and diabetes in three large cities in South Asia: The Center for cArdio-metabolic Risk Reduction in South Asia (CARRS) Study. Issue 2 (November 2015) - Deepa, Mohan; Grace, Mundu; Binukumar, Bhaskarapillai; Pradeepa, Rajendra; Roopa, Shivashankar; Khan, Hassan M.; Fatmi, Zafar; Kadir, Muhammad M.; Naeem, Imran; Ajay, Vamadevan S.; Anjana, Ranjit Mohan; Ali, Mohammed K.; et al.
Abstract: Aim: To estimate the prevalence of, and assess factors associated with, diabetes and prediabetes in three South Asian cities. Methods: Using a multi-stage cluster random sample representative of each city, 16, 288 subjects aged ≥20 years (Chennai: 6906, Delhi: 5365 and Karachi: 4017) were recruited to the Centre for cArdio-metabolic Risk Reduction in South-Asia (CARRS) Study. Fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c) were measured in 13720 subjects. Prediabetes was defined as FPG 100–125 mg/dl (5.6–6.9 mmol/l) and/or HbA1c 5.7–6.4% (39–46 mmol/mol) and diabetes as self-report and/or drug treatment for diabetes and/or FPG ≥ 126 mg/dl (≥7.0 mmol/l) and/or HbA1c ≥ 6.5% (48 mmol/mol). We assessed factors associated with diabetes and prediabetes using polytomous logistic regression models. Results: Overall 47.3–73.1% of the population had either diabetes or prediabetes: Chennai 60.7% [95%CI: 59.0–62.4%] (diabetes – 22.8% [21.5–24.1%], prediabetes – 37.9% [36.1–39.7%]); Delhi 72.7% [70.6–74.9%] (diabetes – 25.2% [23.6–26.8%], prediabetes – 47.6% [45.6–49.5%]); and Karachi 47.4% [45.7–49.1%]; (diabetes – 16.3% [15.2–17.3%], prediabetes – 31.1% [29.5–32.8%], respectively). Proportions of self-reported diabetes were 55.1%, 39.0%, and 48.0% in Chennai, Delhi, and Karachi, respectively. City, age, family history of diabetes, generalized obesity, abdominal obesity, body fat, high cholesterol, high triglyceride, and low HDL cholesterol levels were each independently associated with prediabetes, while the same factors plus waist-to-height ratio and hypertension were associated with diabetes. Conclusion: Six in ten adults in large South Asian cities have either diabetes or prediabetes. These data call for urgent action to prevent diabetes in South Asia.